Randomised controlled trials and clinical maternity care: moving on from intention-to-treat and other simplistic analyses of efficacy - AW Welsh (BMC, 2013)
Abstract Background The obstetrical literature is dominated by Randomised Controlled Trials (RCTs), with the vast majority being analysed using an intention-to-treat (ITT) approach. Whilst this approach may reflect well the consequence of assignment to therapy and hence the 'trialists'perspective', it may fail to address the consequence of actually receiving therapy (the patient's perspective). Discussion This review questions the ubiquitous adherence to the ITT approach, and gives examples of where this may have misled the maternity care professions. It gives an overview of techniques to overcome potential deficiencies in result presentation, using method effectiveness models such as 'Per Protocol' (PP) or 'As-Treated' (AT) that may give more accurate clinical meaning to the presentation of obstetrical results. It then proceeds to cover the added benefits, considerations and potential pitfalls of the use of Instrumental Variable (IV) models in order to better reflect the clinical context. Summary While ITT may achieve statistical purity, it frequently fails to address the true clinical or patient's perspective. Though more complex and potentially beset by problems of their own, alternative methods of result presentation may better serve the latter aim. Each of the other methods may rely on untestable assumptions and therefore it is wisest that study results are presented in multiple formats to allow for informed reader evaluation.